The Effect of Marketing Mix on Customer Satisfaction Level at Bank Sumsel Babel Pagar Alam Branch: A Case Study of Hajj Savings in 2021-2023 - Dewi, Dismita Citra; Agustina, Ranti (Jurnal EMT KITA, 2025)
This study aims to analyze the extent to which the marketing mix which includes product elements, prices, locations, and promotions affects the level of customer satisfaction with hajj savings services at Bank Sumsel Babel Pagaralam City Branch. The methodology used is a quantitative approach, where data is collected through a questionnaire distributed to 86 respondents who are active customers of the Hajj Tasbih Savings. The data obtained was analyzed using multiple linear regression to assess the influence of each variable simultaneously and partially on customer satisfaction. The results of the analysis show that together, the four components of the marketing mix have a significant influence on the level of customer satisfaction. However, when viewed separately, only the Places variable with a value of 0.018 < 0.05 and a promotion with a value of 0.002 < 0.05 were shown to have a significant effect, while the product variable with a value of 0.067 > 0.05 and a price with a value of 0.843 > 0.05 showed no influence meaning these findings confirm that service accessibility and promotional effectiveness play an important role in shaping customer satisfaction. Therefore, banks are advised to improve marketing strategies, especially in terms of improving product quality and price adjustments, in order to encourage customer loyalty and satisfaction in a sustainable manner.